A Study on the Veil and Attire of Zoroastrian Women's in the Safaviet Era - Ali Akbar Jafari (Taḥqīqāt-i Farhangī-i Īrān)
The Safaviet regime introduced a new identity to Iranians that was based on the Shiite religion. The teachings of this religion gradually became manifested in the speech and the behavior of the society. Some non-Moslem minorities lived in different cities and regions and followed their own religious believes and traditional conduit. The Zoroastrians were the renowned minority among all. Therefore, the historians and European travelers of that era became interested in Zoroastrian's way of living. The women's attire and veiling and the related images of this social behavior were either described or captured on the paper and this raises the question that: what kind of variables did influence the Veiling and attire of the Zoroastrian women in that era? In order to answer this question the following assumption should be examined ''The Zoroastrian religious teachings and the emphasis on Veil in Iran as a necessity for women together with the religious teachings of shiiet in the Safviet era were dominant and played an essential role in the Zoroastrian women's Veiling and attire'' The subject of this study is in the historical sociology. Here the historic-analytic method is applied and the data is obtained from to domestic historians and European travelers' recorded notes of the ear. In the conceptual analysis the historical findings are studied by adopting functionalism in the field of sociology. Based on these two typs of study the essential outcome of this research proves the assumption to be right and indicates that how influential the three essential factors have been regarding the title of this research.